2023
DOI: 10.3389/fmicb.2022.1066133
|View full text |Cite
|
Sign up to set email alerts
|

A minireview on the bioremediative potential of microbial enzymes as solution to emerging microplastic pollution

Abstract: Accumulating plastics in the biosphere implicates adverse effects, raising serious concern among scientists worldwide. Plastic waste in nature disintegrates into microplastics. Because of their minute appearance, at a scale of <5 mm, microplastics easily penetrate different pristine water bodies and terrestrial niches, posing detrimental effects on flora and fauna. The potential bioremediative application of microbial enzymes is a sustainable solution for the degradation of microplastics. Studies have r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 119 publications
(102 reference statements)
0
1
0
Order By: Relevance
“…In addition, several studies have noted the microalgae's potential for bioremediation. Numerous functional expression investigations on a diatom and a green alga were conducted [80][81][82][83][84][85][86][87][88][89][90][91]. A study by Mohanan et al unveiled that intracellular lipases can be cloned and expressed [92].…”
Section: Innovative Biotechnological Methods To Augment Enzyme Activi...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, several studies have noted the microalgae's potential for bioremediation. Numerous functional expression investigations on a diatom and a green alga were conducted [80][81][82][83][84][85][86][87][88][89][90][91]. A study by Mohanan et al unveiled that intracellular lipases can be cloned and expressed [92].…”
Section: Innovative Biotechnological Methods To Augment Enzyme Activi...mentioning
confidence: 99%
“…Metagenomicbased research revealed the presence of nearly 800 or more PET hydrolases in the strains of archaea and bacteria from terrestrial and marine environments. Pseudomonas pelagia cutinase is involved in the degradation of polyester [80]. P. pertucinogena can also be used to clean polyesters [81].…”
Section: Chemical Technologiesmentioning
confidence: 99%
“…Degradative Enzymes: Bacteria are essential to bioremediation because they produce a range of enzymes that help break down contaminants. As an illustration, certain bacteria produce oxygenases, which initiate the oxidation reactions that degrade hydrocarbons, including PAHs [13]. Formation of Biofilms: Bacterial biofilms improve the efficiency of pollutant decomposition.…”
Section: Bacterial Bioremediationmentioning
confidence: 99%